2007
DOI: 10.1158/0008-5472.can-06-1378
|View full text |Cite
|
Sign up to set email alerts
|

PEA-15 Inhibits Tumor Cell Invasion by Binding to Extracellular Signal-Regulated Kinase 1/2

Abstract: Phosphoprotein enriched in astrocytes of 15 kDa (PEA-15) binds to extracellular signal-regulated kinase 1 and 2 (ERK1/2) mitogen-activated protein (MAP) kinases to alter ERK1/2 cellular localization and target preferences and binds to adaptors in the extrinsic cell death pathway to block apoptosis. Here, we report that PEA-15 protein expression is inversely correlated with the invasive behavior of breast cancer in an immunohistochemical analysis of a breast cancer progression tissue microarray. Short hairpin R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
76
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 50 publications
10
76
0
Order By: Relevance
“…The inhibitory effects of PEA15 on the growth of breast cancer cells and its ability to counteract the antiestrogen resistance of MCF7 cells overexpressing BCAR3 together with previous data showing a correlation of high PEA15 expression with benign markers and low invasiveness in clinical breast cancer specimens (54,56) suggest that tumors with high PEA15 levels are less malignant than tumors with low PEA15. Thus, PEA15 protein expression should be considered when evaluating the prognostic significance of BCAR1 and BCAR3 in breast cancer specimens (4, 5, 14, 18, 19).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The inhibitory effects of PEA15 on the growth of breast cancer cells and its ability to counteract the antiestrogen resistance of MCF7 cells overexpressing BCAR3 together with previous data showing a correlation of high PEA15 expression with benign markers and low invasiveness in clinical breast cancer specimens (54,56) suggest that tumors with high PEA15 levels are less malignant than tumors with low PEA15. Thus, PEA15 protein expression should be considered when evaluating the prognostic significance of BCAR1 and BCAR3 in breast cancer specimens (4, 5, 14, 18, 19).…”
Section: Resultssupporting
confidence: 60%
“…Previous studies reported that PEA15 inhibits breast cancer cell growth and invasiveness concomitant with sequestration of cytoplasmic ERK1/2 but did not demonstrate the importance of ERK1/2 binding in the growth effects of PEA15, a protein capable of multiple activities (54,56,67). Interestingly, high PEA15 protein expression in breast cancer clinical samples has been significantly correlated with positive estrogen/progesterone receptor status and a low level of the proliferation marker, proliferating cell nuclear antigen (54).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer patients, low PEA-15 expression was previously linked with aggressive forms of the disease. Similarly, greater PEA-15 expression was associated with less invasion in breast cancer through effects on the ERK pathway [17]. We also found that PEA-15 expression levels were lower in high-grade than in low-grade breast tumors.…”
Section: Discussionsupporting
confidence: 63%
“…[91] The same strategy is utilized for the induction of apoptosis, by the pro-apoptotic protein Bik, in lung epithelial cells [92] and by the death-associated…”
Section: Local Intervention For the Prevention Of Global Malignancy?mentioning
confidence: 99%
“…As mentioned before, sequestering ERKs at the cytoplasm, whereby ERKs nuclear signals are impeded, is sufficient for abrogating growth and/ or potentiating apoptosis. [91][92][93] Recently, a nuclear translocation signal: Ser-Pro-Ser, has been identified within ERKs ''insert.'' These serines are phosphorylated upon stimulation, promoting ERKs translocation to the nucleus.…”
Section: Local Intervention For the Prevention Of Global Malignancy?mentioning
confidence: 99%